Pengaruh Biaya Produksi dan Volume Penjualan terhadap Laba Bersih di Padu Padan Tenun - Anastasya Debora Benyamin; Herly M. Oematan; Rikhard T. C. Bolang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effects of production costs and sales volume on net profit at Padu Padan Tenun in Kupang City, East Nusa Tenggara. The sample comprises monthly data on production costs, sales volume, and net profit for the period 2020–2023, totaling 48 observations. The data used are secondary data obtained from Padu Padan Tenun. The data analysis techniques employed are the classical assumption test and multiple linear regression analysis. The results of this study indicate that, simultaneously, production costs and sales volume have a significant effect on net profit. Partially, production costs have a negative and significant effect on net profit, while sales volume has a positive and significant effect.